Suicidal Self-Harm Behaviors in Young Adult Women - Geovanny Serviam Permana Putri Rahamitu; Meidiana Dwidiyanti; Luky Dwiantoro (GLOBAL HEALTH SCIENCE GROUP, 2024)
Self-harm is a rising concern among young adult women, particularly as it is often linked to an increased risk of suicide. This study aims to examine the patterns, motivations, and psychological impacts of self-harm behaviors within this demographic, focusing on the underlying emotional triggers and contextual factors. Using a qualitative approach, in-depth interviews were conducted with participants aged 18 to 25 years who had experienced self-harming behaviors. The method allowed for a detailed exploration of their personal experiences, revealing that self-harm frequently serves as a coping mechanism to manage intense emotional pain and a perceived lack of control over negative emotions. Participants often reported that self-harm provided temporary relief, though it sometimes led to feelings of regret and shame. Additionally, a significant portion of the participants expressed a tenuous connection between self-harm and suicidal ideation, highlighting a complex relationship between self-harm and mental health risks without a direct intent to commit suicide. This study underscores the need for targeted, empathetic interventions that address the emotional and psychological needs of young adult women struggling with self-harm, providing insights for mental health practitioners to develop tailored support strategies aimed at reducing self-harm and related mental health challenges in this population.